2013
DOI: 10.1007/s12262-013-0998-x
|View full text |Cite
|
Sign up to set email alerts
|

Picture Archiving and Communication System (PACS): Clinician’s Perspective About Filmless Imaging

Abstract: Picture archiving and communication systems (PACS) are most appropriate means of acquiring, archiving, and communicating all forms of radiology imaging. The present study is to decide applicability of PACS, its exact role in patient care, and benefit as a teaching tool. To compare conventional imaging with picture archiving and communication system from user's point of view, impact of PACS on patient care and teaching. This was a single center, observational study over a period of 4 weeks from 15 January 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
2
8
3
2
Order By: Relevance
“…The results of the mentioned studies are consistent with the present study's findings. However, the present study's results about comparing the ease of use in PACS and the traditional system differ somewhat from Jorwekar and colleagues' study [36]in which system users described the PACS as being very user-friendly. Perhaps this level of difference in opinions about the easiness in using PACS compared to traditional film-based systems is related to the computer literacy level of the users and or the lake of interoperability of PACS with other health information systems.…”
Section: Pacs Versus Traditional Radiologycontrasting
confidence: 98%
See 1 more Smart Citation
“…The results of the mentioned studies are consistent with the present study's findings. However, the present study's results about comparing the ease of use in PACS and the traditional system differ somewhat from Jorwekar and colleagues' study [36]in which system users described the PACS as being very user-friendly. Perhaps this level of difference in opinions about the easiness in using PACS compared to traditional film-based systems is related to the computer literacy level of the users and or the lake of interoperability of PACS with other health information systems.…”
Section: Pacs Versus Traditional Radiologycontrasting
confidence: 98%
“…A study by Buabbas and colleagues [10], findings showed that more than three-quarters of the radiologists and technologists, consider using PACS as positive and being user-friendly. Also, Jorwekar and colleagues [36] in their study addressed the easiness in using PACS in users' viewpoints and reported that 85% of the users believed that PACS was very easy to use for them. The results of the mentioned studies are consistent with the present study.…”
Section: System's Ease Of Usementioning
confidence: 99%
“…This system is an electronic and preferably filmless data system for obtaining, sorting, transporting, putting away and electronically displaying health care images and data. 12 Digital imaging vendors push this system profits, counting the end of unreasonable silverbased film, progressed access to new and old movies for all clinicians, lessening in the physical stockpiling prerequisite of massive movies, and more level work force costs. In this paper, a restricted client study was attempted at the Hospital Sungai Buloh, Malaysia, in cooperation with the UPM preceding the advancement of the web program engineering with numerous fewer clients having admittance to the system.…”
Section: Discussionmentioning
confidence: 99%
“…1,11 DR merupakan kelas detektor digital yang menghasilkan gambar tanpa penanganan lebih lanjut dari detektor, di mana gambar x-ray laten dikonversi ke gambar digital dalam interval segera setelah paparan (Gambar 2). 12,13,14 Secara umum, perbandingan antara sistem CR dan DR ditampilkan pada Tabel 1.…”
Section: Modalitas Akuisisi Pencitraanunclassified
“…Kemampuan workstation yang dapat meningkatkan produktivitas dokter tercantum dalam Tabel 6. 1,23,27,28 Opsi atau Fungsi Tujuan…”
Section: Sistem Penampil Gambarunclassified